2011
DOI: 10.1103/physrevlett.107.144303
|View full text |Cite
|
Sign up to set email alerts
|

Ageing of a Microscopic Sliding Gold Contact at Low Temperatures

Abstract: Nanometer-scale friction measurements on a Au(111) surface have been performed at temperatures between 30 and 300 K by means of atomic force microscopy. Stable stick slip with atomic periodicity is observed at all temperatures, showing only weak dependence on temperature between 300 and 170 K. Below 170 K, friction increases with time and a distortion of the stick-slip characteristic is observed. Low friction and periodic stick slip can be reestablished by pulling the tip out of contact and subsequently restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…In Ref. [6], Gosvami et al investigated the ageing of single-asperity sliding contacts between an AFM-tip and an Au(111) surface at low temperature and under UHV conditions. There the authors also observed stable stick-slip with atomic periodicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. [6], Gosvami et al investigated the ageing of single-asperity sliding contacts between an AFM-tip and an Au(111) surface at low temperature and under UHV conditions. There the authors also observed stable stick-slip with atomic periodicity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to single-asperity friction measurements performed in ultra-high vacuum (UHV)-conditions in Refs. [5,6], the authors reported on 2 / 3 n F -dependence of the friction force on gold nanoparticles measured in ambient conditions, where F n is the normal force [8]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,15], unraveling the underlying specific molecular processes in quantitative detail. Further possible aging mechanisms are the formation of capillary bridges in a humid environment [16] and the formation of a neck due to material transfer from the substrate into the contact region with the tip [17]. Finally, recent molecular-dynamics simulations revealed that the AFM tip may, in the course of time, evolve into a different geometrical contact configuration characterized by a different energy of binding to the surface [18].…”
mentioning
confidence: 99%
“…The basic idea of our model is that, in any given stick phase, the tip-sample contact may either break, resulting in a slip event, or strengthen itself by one of the molecular aging mechanisms described above [13][14][15][16][17][18]. Within our minimal model, we assume just two possible stick states of the AFM tip: a weakly bound state A and a strongly bound state B (see Fig.…”
mentioning
confidence: 99%